Frequency dependency of power system loads - Ayaz, Almasbek (My University, 2024)
Abstract The growing interest in examining power system loads is driven by the increasing integration of variable generation units into the distribution network. At the distribution level, load representation will involve smaller aggregates, such as smaller customer groups, resulting in aggregate load models and network performance being more sensitive to variations within the individual load components. As technological advancements in power systems emerge, it necessitates a more detailed representation of both the distribution network and the electrical characteristics of connected loads. This study aims to understand the behaviour of these loads and investigate whether requency dependency will become a critical parameter in future power system networks. Laboratory experiments were conducted to examine the frequency characteristics for both static and dynamic loads based on active and reactive power consumption. With the help of MATLAB analysing software, it was observed that static loads separately exhibited some frequency dependence; however, considering the combination of loads under evaluation, the frequency dependence coefficients are insignificant. This information enables a more thorough understanding of frequency dependence of loads.
Keywords: Keywords: Power system, Load modelling, Frequency dependence, Load frequency characteristics, LED lightning, Induction machine, Electric heater.